2019
DOI: 10.2308/jmar-52547
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Operating Performance During Economic Slowdowns

Abstract: Operating performance is an important and widely used measure for evaluating firms. This paper documents that, contrary to the common belief, firms experiencing sales declines during economic slowdowns exhibit higher operating margins than firms experiencing sales declines during normal periods. This anomalous behavior results from (1) a decrease in costs of goods sold overall during economic slowdowns and (2) an additional reduction in SG&A costs other than expenditures that could affect the competitivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“…, specifically and in detail, reviewed the asymmetry of cost behavior in their article in 2014. In addition, Banker also examined the implications of the existence of cost behavior asymmetry in financial statement analysis (Anderson et al, 2007;Bu et al, 2015), the effect of cost behavior asymmetry related to conservatism (Banker et al, 2016), as well as the dominant factors affecting the asymmetry of cost behavior, including the magnitude of changes in sales , worker protection rules (Banker et al, 2013), and, most recently, macroeconomic conditions (Banker et al, 2020). Finally, the results of the bibliometric analysis show the keywords that are often used by cost stickiness researchers.…”
Section: Resultsmentioning
confidence: 99%
“…, specifically and in detail, reviewed the asymmetry of cost behavior in their article in 2014. In addition, Banker also examined the implications of the existence of cost behavior asymmetry in financial statement analysis (Anderson et al, 2007;Bu et al, 2015), the effect of cost behavior asymmetry related to conservatism (Banker et al, 2016), as well as the dominant factors affecting the asymmetry of cost behavior, including the magnitude of changes in sales , worker protection rules (Banker et al, 2013), and, most recently, macroeconomic conditions (Banker et al, 2020). Finally, the results of the bibliometric analysis show the keywords that are often used by cost stickiness researchers.…”
Section: Resultsmentioning
confidence: 99%
“…According to Anderson et al (2003), costs are sticky when they respond to business activity augments more than to contemporaneous activity reductions. The level of cost stickiness is determined by three factors: managerial empire building incentives, adjustment costs, and managerial expectations (Anderson et al, 2003; Banker et al, 2020; Chen et al, 2012).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Accordingly, they will utilize these resources after the demand recovers, which can increase firm’s cost stickiness. On the contrary, pessimistic managers would decrease unused resources (Banker et al, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Additionally, Banker, Fang and Mehta (2020) have found that the decisions of the managers are complex and affected by the company's information and the environmental economic conditions in which it is located. Thus, the economic slowdown tends to play a distinct and important role in the operational decisions of managers, such as raise incentives to preserve cash; increase pessimism about future sales prospects; and facilitate organizational restructuring to improve efficiency.…”
Section: Corporate Governance Stock Market Volatility and Economic Environmentmentioning
confidence: 99%